Inflation, Uncertainty, and Growth in Colombia - Ma, Henry (IMF Working Papers; Working Paper ;, 1998)
It has been argued that higher levels of inflation lead to greater uncertainty about future inflation and to greater dispersion of relative prices. In either case, inflation could reduce the efficiency of market prices in coordinating economic activities. This paper shows that the rise of inflation in Colombia, from low levels in the 1950s to average rates of 18-22 percent since the 1970s, has been accompanied by increased uncertainty and relative price dispersion; and that inflation has had a negative and persistent effect on real GDP growth.